How far does physical training modulate the motor unit activities of respiratory muscles in female athletes: an electromyographic study - Nandy, P.; Bandyopadhyay, A. (American Journal of Sports Science, 2021)
The pulmonary capacities of a person depend on the activities of the respiratory muscles. The Motor neurons and its units of the respiratory muscles regulate breathing and can be studied by using surface electromyography. The effect of physical training on motor unit involvement was the main concern of this study and the other is to understand the influence of physical exercise on respiratory muscles. It has focused on the associative strength in motor units during forceful and normal respiration of 15-20 years young female and nonathletes. The sEMG has the delicate and respiratory interplay or coordination of muscles recorded by placing the electrodes on the preferred anatomical places of three selected muscles in standing postures of thirty-eight trained female athletes and thirty-three nonathletes. Spirometric studies were performed simultaneously during normal and forceful respiration in each subject. One way ANOVA, Scheffe's multiple comparison tests, and Strength of association during different types of respiration were calculated. A significant difference has been observed in motor unit activity among the three muscles during maximum and normal respiration. Scheffe's multiple comparison tests showed the difference between Intercostal and Latissimus dorsi, Diaphragm, and Latissimus dorsi muscles in athletes during normal and forceful respiration. In nonathletes, significant differences were observed between Intercostal and diaphragm, Diaphragm, and Latissimus dorsi muscles only during normal respiration. But during forceful respiration, insignificant differences among the three muscles in females were observed in nonathletes. The strength of association of motor units for respiratory muscles and the duration of muscle responses are lower in athletes during normal and forceful respiration. But, motor unit activity is higher in athletes in all conditions. It means athletes produce better responses though there is a little motor unit involved. It has also been seen that the duration of EMG bursts, i.e. muscle response time is lower in athletes than nonathletes. So, this study concluded that with fewer motor units, athletes could produce more significant respiratory, muscular activity in less time and less associative strength than the non-athletes. It assumed that due to physical training, muscles improved pulmonary capacities by increasing the flexibility of respiratory muscles.